Area deprivation levels of members of a fully digital diabetes prevention program compared to the US population - Pickus, Sarah K.; Lockwood, Kimberly G.; Graham, Sarah A. (Frontiers in Endocrinology, 2025)
BackgroundDeprived geographic areas have high rates of poverty, unemployment, low education, and limited access to health care, which can lead to poor health outcomes. Fully digital deliveries of the National Diabetes Prevention Program (DPP) can offer accessible preventive healthcare to individuals living in deprived areas, but this does not necessarily mean that these individuals will participate in digital health solutions. There is a pervasive belief that digital solutions are only used by socially advantaged groups.ObjectiveDetermine whether a fully digital DPP has uptake in individuals residing in areas with high deprivation levels to substantiate that digital solutions can help overcome barriers to diabetes care.MethodsAn observational study comparing area deprivation levels of N=41,375 digital DPP members with commercial insurance and N=844 with Medicaid to that of US adults with either commercial insurance or Medicaid coverage. Data sources included demographic and geographic data from members enrolled during or after 2016 in the digital DPP, the 2020 Area Deprivation Index (ADI) v3.2 dataset, and Table B27010 from the 2016–2020 American Community Survey.ResultsDigital DPP members with commercial insurance lived in areas with higher deprivation than the commercially insured US population, D=0.13, p<.001. ADI quintile 1 (least deprived) represented 14.7% of digital DPP members vs. 22.5% of the US population; quintile 5 (most deprived) represented 19.2% of digital DPP members vs. 13.2% of the US population. Digital DPP members with Medicaid coverage lived in areas with higher deprivation than the comparable Medicaid-covered US population, D=0.35, p<.001. ADI quintile 1 represented 0.4% of digital DPP members vs. 16.7% of the Medicaid population, and quintile 5 represented 50.0% of digital DPP members vs. 26.6% of the Medicaid population.ConclusionsThis study demonstrates that a digital DPP had uptake in individuals with prediabetes who lived in areas with higher deprivation than the comparable US population. This finding suggests that a digital DPP indeed reached individuals in high deprivation areas in need of accessible preventive healthcare, contradicting the stereotype that digital solutions only reach socially advantaged individuals with prediabetes. Providing much-needed, on-demand care may help to mitigate the associated negative health impacts of living in a deprived area.